A mode-of-action ontology model for safety evaluation of chemicals: Outcome of a series of workshops on repeated dose toxicity. (September 2019) - Desprez, Bertrand; Birk, Barbara; Blaauboer, Bas; Boobis, Alan; Carmichael, Paul; Cronin, Mark T.D.; Curie, Richard; Daston, George; Hubesch, Bruno; Jennings, Paul; Klaric, Martina; Kroese, Dinant; et al.
Abstract: Repeated dose toxicity evaluation aims at assessing the occurrence of adverse effects following chronic or repeated exposure to chemicals. Non-animal approaches have gained importance in the last decades because of ethical considerations as well as due to scientific reasons calling for more human-based strategies. A critical aspect of this challenge is linked to the capacity to cover a comprehensive set of interdependent mechanisms of action, link them to adverse effects and interpret their probability to be triggered in the light of the exposure at the (sub)cellular level. Inherent to its structured nature, an ontology addressing repeated dose toxicity could be a scientific and transparent way to achieve this goal. Additionally, repeated dose toxicity evaluation through the use of a harmonized ontology should be performed in a reproducible and consistent manner, while mimicking as accurately as possible human physiology and adaptivity. In this paper, the outcome of a series of workshops organized by Cosmetics Europe on this topic is reported. As such, this manuscript shows how experts set critical elements and ways of establishing a mode-of-action ontology model as a support to risk assessors aiming to perform animal-free safety evaluation of chemicals based on repeated dose toxicity data. Highlights: A repeated dose toxicity mode-of-action ontology model consisting of 4 pillars is proposed. Pillar 1 and 2 relate to kinetic and chemical aspects, respectively. Pillar 3 and 4 relate to mechanistic and toxicological aspects, respectively. The repeated dose toxicity mode-of-action ontology model can serve safety evaluation purposes.